Analysis Of Acceptance Factors Of Tiket Pendakian Application Using UTAUT - Moch. Abdillah Emha Ramdhani; Anita Wulansari; Tri Puspa Rinjeni (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The popularity of mountain climbing has created a need for an efficient and user-friendly reservation system. However, in December 2024, the Tiket Pencakian application only received a rating of 3.9 on digital platforms, reflecting user dissatisfaction with the application's functionality and user experience. Complaints included unstable connections and login failures. The purpose of this study was to analyze the factors influencing user acceptance of the Tiket Pencakian application using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This study applied a quantitative approach through an online questionnaire distribution, which successfully collected 390 respondents from various regions in Indonesia. After the data cleaning process, 371 valid data were analyzed using the Partial Least Square technique through SmartPLS 3 software. The research model includes nine hypotheses that measure the influence between factors on the intention and actual behavior of using the application. The results of the study proved that six hypotheses were significantly accepted, including Performance Expectancy, Social Influence, Hedonic Motivation, and Habit having a significant positive effect on Behavioral Intention, and Behavioral Intention and Habit having a positive and significant effect on ICT Usage Behavior. Meanwhile, Effort Expectancy and Facilitating Conditions on Behavioral Intention, as well as Facilitating Conditions on ICT Usage Behavior, did not have a significant effect. It can be concluded that perceived usefulness, social influence, enjoyment of use, habits, and intention to use are the main factors that shape user behavior in using the Tiket Pendakian application.